Recomendación sobre pruebas de función pulmonar durante la pandemia por coronavirus COVID-19. Junio 2020 - Alvarez G., Cecilia; Borzone T., Gisella; Céspedes G, Juan; Corrales V., Raúl; Gutiérrez C., Mónica; Schonffeldt G., Patricia (Revista Chilena de Enfermedades Respiratorias, 2020)
n